Profiling disease experience in patients living with brain aneurysms by analyzing multimodal clinical data and quality of life measures - Sebastian R. Reder; Jochen Hardt; Marc A. Brockmann; Carolin Brockmann; Suam Kim; Melina Kawulycz; Marie Schulz; Sven Rainer Kantelhardt; Katja Petrowski; Sabine Fischbeck (Scientific Reports)
Abstract To explore the mental and physical health (MH, PH) on individuals living with brain aneurysms and to profile their differences in disease experience. In N = 111 patients the Short Form 36 Health Survey (SF-36) was assessed via an online survey; Supplementary data included angiography and magnetic resonance imaging (MRI) findings (including AI-based brain Lesion Volume analyses in ml, or LV). Correlation and regression analyses were conducted (including biological sex, age, overall brain LV, PH, MH). Disease profiles were determined using principal component analysis. Compared to the German normative cohort, patients exhibited overall lower SF-36 scores. In regression analyses, the DW was predictable by PH (β = 0.345) and MH (β=-0.646; R = 0.557; p < 0.001). Vasospasm severity correlated significantly with LV (r = 0.242, p = 0.043), MH (r=-0.321, p = 0.043), and PH (r=-0.372, p = 0.028). Higher LV were associated with poorer PH (r=-0.502, p = 0.001), unlike MH (p > 0.05). Main disease profiles were identified: (1) those with increased LV post-rupture (high DW); (2) older individuals with stable aneurysms (low DW); (3) revealing a sex disparity in QoL despite similar vasospasm severity; and 4), focused on chronic pain and its impact on daily tasks. Two sub-profiles highlighted trauma-induced impairments, functional disabilities from LV, and persistent anxiety. Reduced thalamic and pallidal volumes were linked to low QoL following subarachnoid hemorrhage. MH has a greater impact on life quality compared to physical disabilities, leading to prolonged DW. A singular physical impairment was rather atypical for a perceived worse outcome. Patient profiles revealed that clinical history, sex, psychological stress, and pain each contribute uniquely to QoL and work capacity. Prioritizing MH in assessing workability and rehabilitation is crucial for survivors’ long-term outcome.